Laboratory Performance Modeling using Petri Nets in National Standardization Agency in Indonesia - Manahan Siallagan; Chao Ou-Yang; Nikolaus Aloysius (Research Synergy Foundation, 2022)
Service providers perform their service to seek customer loyalty, not excluding the product testing laboratory (PTL) as it provides the testing service under National Standardization Agency (NSA) in Indonesia. Early business process observation in one PTL found that the level of work-in-progress (WIP) in some testing job shops performed significantly higher than the others which requires a further operational study. Using workflow data from the PTL, this study modeled the first-come-first-serve (FCFS) as the current scheduling algorithm, proposed an alternative scheduling algorithm, and comparatively analyze the WIP performance through simulation using colored Petri nets (CPN) as business process modeling and simulation tools. The result of this study shows that the shortest flow of processing time (SFPT) algorithm as the alternative scheduling strategy can reduce the maximum WIP level in the laboratory. Although the SFPT scheduling strategy has a relatively small impact in the single item station, the alternative strategy decreases more than one-third of the total WIP in the most complex station in the laboratory.